Analisis Hukum Islam dalam Pelaksanaan Bimbingan Perkawinan Sebagai Upaya Mempersiapkan Keluarga Sakinah - Septi Khoirunnisa; Suprihatin; Musyaffa Amin Ash Shabah (Universitas Pangeran Diponegoro Nganjuk, 2026)
This research is motivated by the importance of marriage guidance conducted by the KUA (Religious Affairs Office) in each region, especially the West Bekasi KUA. The purpose of this study is to determine how the implementation of marriage guidance in the West Bekasi KUA is reviewed from the concept of Islamic law, which is a form of effort to prepare a sakinah, mawaddah, wa rahmah family. The research method used is descriptive qualitative by conducting interviews with the head and staff of the West Bekasi KUA, then the data is analyzed. The results of the study indicate that the implementation of marriage guidance conducted in the West Bekasi KUA is in accordance with the principles of Islamic law and applicable laws stipulated in the Decree of the Director General of Islamic Community Guidance No. 172 of 2022 concerning technical and operational guidelines for marriage guidance. This can be seen from the implementation of marriage guidance which includes the person in charge of implementing guidance, materials, speakers, methods, types of guidance and the nature of the implementation of guidance. Therefore, the implementation of marriage guidance supports in preparing a sakinah family, which in its material contains various aspects including spiritual, emotional, social, economic, and health aspects.